2017
DOI: 10.17221/139/2016-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Wheat resistance to Fusarium head blight and possibilities of its improvement using molecular marker-assisted selection

Abstract: Shah L., Ali A., Zhu Y., Wang S., Si H., Ma C. (2017): Wheat resistance to Fusarium head blight and possibilities of its improvement using molecular marker-assisted selection. Czech J. Genet. Plant Breed., 53: 47−54.Wheat, one of the world's major crops, is seriously affected by fungal diseases, especially in regions with high moisture and moderately warm temperatures. This paper reviews various molecular and conventional techniques that are used to identify genotypes with resistance alleles associated with Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Although complete FHB resistance has not been obtained yet ( Steiner et al, 2017 ), identification and validation of major and minor effect QTLs and their introgression through diverse breeding methodologies including recently implemented methods such as marker-assisted and genomic selections are of paramount important. These methods have allowed gene pyramiding for durable resistance across wheat breeding programs ( Buerstmayr et al, 2009 ; Li et al, 2016b ; Shah et al, 2017 ; Zhao et al, 2018 ; Zhu et al, 2019 ). Meanwhile, the catastrophic epidemics in the 1990s resulted in the initiation of the US wheat and barley scab initiative (USWBSI; ) in 1997 ( McMullen et al, 2012 ).…”
Section: Epidemiology and Management Of Fhbmentioning
confidence: 99%
See 2 more Smart Citations
“…Although complete FHB resistance has not been obtained yet ( Steiner et al, 2017 ), identification and validation of major and minor effect QTLs and their introgression through diverse breeding methodologies including recently implemented methods such as marker-assisted and genomic selections are of paramount important. These methods have allowed gene pyramiding for durable resistance across wheat breeding programs ( Buerstmayr et al, 2009 ; Li et al, 2016b ; Shah et al, 2017 ; Zhao et al, 2018 ; Zhu et al, 2019 ). Meanwhile, the catastrophic epidemics in the 1990s resulted in the initiation of the US wheat and barley scab initiative (USWBSI; ) in 1997 ( McMullen et al, 2012 ).…”
Section: Epidemiology and Management Of Fhbmentioning
confidence: 99%
“…FHB resistance is partially additive, so gene pyramiding is feasible using marker-assisted backcrossing or using either a single or combination of different selection strategies including phenotypic selection, MAS, and GS ( Figure 3 ) ( Shah et al, 2017 ). Agostinelli et al (2012) suggested that an initial round of phenotypic selection for FHB traits at a moderate intensity will increase the homozygous resistant alleles at the major locus thus intensifying the MAS in the next round.…”
Section: Genetics Of Fhb Resistance and Breeding Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tolerant breeding lines have been developed, with associated molecular markers (Shah et al ., ,b). An example is the Fhb1 gene from the Chinese wheat cultivar Sumai 3 (Rawat et al ., ).…”
Section: Host Resistance To Fusarium Infectionmentioning
confidence: 99%
“…As far as the vulnerability of a cultivar to FHB and DON is concerned, breeding improvement in cereals, using conventional methods, molecular markers or via transgenic methods have been described in several reviews (Hollins et al ., ; Snijders, ; Shah et al ., ,b). Arthur () was the first to observe variation in vulnerability to FHB among wheat cultivars.…”
Section: Host Resistance To Fusarium Infectionmentioning
confidence: 99%